The Motivation to Work and Environmental Influences Working Against Employees of The Employment Department of Education, Youth and Sports District Minahasa - Roddy Albert Runtuwarouw; Jerry RH Wuisang (Journal of International Conference Proceedings (JICP), 2018)
This research was conducted to find out the influence of motivational work environment and work towards the achievements of the work of employees in the Department of education, youth and sports District of Minahasa. The method used is correlational which focuses on a discussion of the relationship between variables X and Y variables. the working environment supports the work and the high motivation of working employees will encourage the creation of good working achievements among employees. Theoretically work environment and work motivation will work together to form a pribasi employee who upholds the job and always maintain good relations or relations with fellow officers and superiors that ultimately gives the feel is good for the improvement of work achievement a clerk in the Office of the Department of education, youth and sports of Minahasa Regency. Evidenced by the magnitude of the results of research influence between variables work environment and motivation the achievement of variable working on education department employees work , youth and sports district Minahasa 63.5 % is simultaneously .This can be concluded that the work environment and motivation can affect the work of 63.5 % department of education employees to work performance , youth and sports district Minahasa .The magnitude of influence between variables x on variables y is 63.5 % where the rest of the percentage of employees work performance to evaluate the department of education , youth and sports district Minahasa 36,5 % is determined by other factors. From these results it appears that the work environment and work motivation alike contribute a sizable work achievement against the employees of the Department of education, youth and sports District of Minahasa. This is because with a conducive environment and the high motivation of creativity will create new and excellent service to the community. Keywords: work environment, motivation work, work performance, employees